Numerical study for diagnosing various malfunctioning modes in PEM fuel cell systems. (14th April 2020) - Chinannai, Muhammad Faizan; Lee, Jaeseung; Ju, Hyunchul
Abstract: The proton exchange membrane fuel cell (PEMFC) is promising technology for efficient power generation and has wide applications. In PEMFC development, it is important to diagnose malfunctions in a system with defective components and a PEMFC stack can act as an effective sensor to detect the various malfunctioning modes. Hence, the focus of this study is to analyze the response of a PEMFC under various malfunction conditions including humidifier, air blower, and coolant pump, catalyst layer degradation, and membrane aging based on 3D PEMFC simulations. Except for the coolant supply malfunction, other malfunctions exhibit similar behavior in terms of voltage drop and temperature rise, requiring more detailed measurement techniques such as Electrochemical Impedance Spectroscopy to identify the cause of malfunctions. In addition, measuring the relative humidity of the outlet gas may not provide sufficient information to distinguish the malfunction of the anode or cathode humidifier. The results of the study suggest fault detection and isolation methods under these malfunction conditions to prevent more severe failure of the PEMFC stack and system. An extensive multi-dimensional contour comprising temperature, relative humidity, liquid saturation, water content, and current density is also provided for the better analyzation of system malfunctioning behaviors. Highlights: Analyzing the Performance of a PEM fuel cell under various malfunctions. 3-D two-phase multi-scale PEMFC model applied to a single cell geometry under various malfunction. Performance degradations of malfunction cases were studied, possible reasons are portrayed. Earlier detection and diagnosis of possible malfunctions considering a stack itself as a good sensor.